Cinta Kasih Refleksi Kritis Atas Intoleransi Kehidupan Beragama Di Indonesia Dari Konsep Cinta Kasih Søren A. Kierkegaard - Poli, Rikhardus; Wijanarko, Robertus (Forum, 2023)
This study focuses on exploring the concept of love according to Soren Kierkegaard's thoughts as a symbol of faith in the midst of the outbreak of religious discrimination in Indonesia. The purpose of this paper is to understand the concept of love according to Soren Kierkegaard and its relevance for religious discrimination that often occurs in Indonesia. Discrimination is common in religious life. The reason is because religion tends to be seen from the building and its rites. The religion that actually contains the values of goodness, truth and the highest value of love is narrowed in meaning. Values whose meaning is very positive and contained in the Scriptures of every religion have narrowed meanings. Religion as a place where the value of love grows is finally sacrificed due to the narrow understanding of its adherents. Soren Kierkegaard gives a very deep understanding of love. This philosopher of existentialism posits about the stages of human life, namely the aesthetic stage, the ethical stage and the religious stage. The concept of love also undergoes changes as human life progresses according to the three stages of human life. The author uses a phenomelogical approach and uses literature studies in completing this paper. According to the author, the concept of love in Kierkegaard's thinking provides the right relevance to the outbreak of religious discrimination that occurred in Indonesia.